Der Wechsel der Sprachen im Gehirn. Neue Einblicke in das ‚code-switching’ mittels funktioneller Kernspintomographie. - Behrent, Sigrid; Franceschini, Rita; Krick, Christoph; Reith, Wolfgang (Magazin Forschung der Universität des Saarlandes)

*Bernhard Pöll, Francophonies périphériques. Histoire, statut et profil des principales variétés du français hors de France. Paris: L’Harmattan 2001, 231p. - Behrent, Sigrid (Vox Romanica)

Der Umgang mit Formularen: Förderung der Lesekompetenz - Albers, Timm (Zeitschrift für Heilpädagogik)

[Rez. v.] Klaus Malettke/Chantal Grell (Hg.): Hofgesellschaft und Höflinge an europäischen Fürstenhöfen in der Frühen Neuzeit (15.–18. Jh.) [...]. Münster u.a. 2001 - Süßmann, Johannes (Historische Zeitschrift)
Keywords: Höfische Gesellschaft

[Rez. v.] Frauke Reitemeier: Deutsch-englische Literaturbeziehungen. Der historische Roman Sir Walter Scotts und seine deutschen Vorläufer (=Beiträge zur englischen und amerikanischen Literatur. 18). Paderborn u.a. Ferdinand Schöningh 2001 - Süßmann, Johannes (IASL online)
Keywords: Geschichtsroman; Scott; Walter; Naubert; Benedikte

[Rez. v.] Stefan Ehrenpreis / Ute Lotz-Heumann: Reformation und konfessionelles Zeitalter (=Kontroversen um die Geschichte), Darmstadt 2002 - Süßmann, Johannes (sehepunkte)
Keywords: Gedenken; Reformation

[Rez. v.] Stephan Mauelshagen: Ordensritter – Landesherr – Kirchenfürst. Damian Hugo von Schönborn (1676–1743). Ein Leben im alten Reich - Süßmann, Johannes (Zeitschrift für württembergische Landesgeschichte)
Keywords: Damian Hugo von Schönborn; Biographie

Einleitung - Dürr, Renate; Engel, Gisela; Süßmann, Johannes (Eigene und fremde Frühe Neuzeiten. Genese und Geltung eines Epochenbegriffs)

Eigene und fremde Frühe Neuzeiten. Genese und Geltung eines Epochenbegriffs

Konstruktion und Validierung eines Fragebogens zur Erfassung der affektiven Bewertung des Übergangs von der Grund- zur weiterführenden Schule - Bloh, Bea; Leffelsend, S. (Diagnose und Intervention in schulischen Handlungsfeldern)

A Hybrid Coding Strategy for Optimized Test Data Compression - Wuertenberger, Armin; S. Tautermann, Christofer; Hellebrand, Sybille (IEEE International Test Conference (ITC'03))

“Wir essen ihn erstmal auf. Das halten wir nicht aus mit der Erinnerung.” Ästhetisch-religiöse Präsentativität in Margarethe von Trottas Jahrestage-Verfilmung - van Laak, Lothar; Jakobs, Silke (Johnson-Jahrbuch 10)

Hermeneutik literarischer Sinnlichkeit. Historisch-systematische Studien zur Literatur des 17. und 18. Jahrhunderts - van Laak, Lothar

hinauskommen-hinauszittern - Elit, Stefan (Goethe-Wörterbuch, Bd. 4, Lfg. 10)

Reaktionszeitmessung: Allgemeinpsychologische Grundlage und psycholinguistische Anwendungen - Scharlau, Ingrid; Ansorge, Ulrich; Neumann, Odmar (Psycholinguistik – Psycholinguistics)

Direct parameter specification of an attention shift: Evidence from perceptual latency priming. - Scharlau, Ingrid; Ansorge, Ulrich (Vision Research)
In the direct parameter specification (DPS) mode of sensorimotor control, response parameters can be specified by stimuli that are not consciously perceived [Psychological Research/Psychologische Forschung 52 (1990) 207]. DPS is contingent on the current intentions. The invisible stimuli can be processed for the purposes of sensorimotor control only if they match the actual intentions, for example, share task-relevant features. The present experiments explore whether attentional capture by masked abrupt-onset stimuli is mediated via DPS. Participants judged which of two visual targets appeared first. Masked primes preceded one of the targets. The primes were either similar to the targets or not, in shape, or in color. Target-like (task-relevant), but not distractor-like (task-irrelevant), primes facilitated perceptual latencies of targets trailing at their positions. Thus, the latency effects resulted from DPS of an attention shift, rather than from bottom-up capture or from top-down
Keywords: direct parameter specification; DPS; attention shift; latency priming; sensorimotor control; stimuli; task-relevant features; visual targets; color; shape; latency effects; Adult; Attention; Discrimination (Psychology); Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Visual Perception; Attention; Perceptual Motor Processes; Response Latency; Stimulus Onset; Visual Stimulation; Form and Shape Perception; Sensory Adaptation

Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional interpretation. - Scharlau, Ingrid; Neumann, Odmar (Psychological Research)
Four experiments investigated the influence of a metacontrast-masked prime on temporal order judgments. The main results were (1) that a masked prime reduced the latency of the mask's conscious perception (perceptual latency priming), (2) that this effect was independent of whether the prime suffered strong or weak masking, (3) that it was unaffected by the degree of visual similarity between the prime and the mask, and that (4) there was no difference between congruent and incongruent primes. Finding (1) suggests that location cueing affects not only response times but also the latency of conscious perception. (2) The finding that priming was unaffected by the prime's detectability argues against a response bias interpretation of this effect. (3) Since visual similarity had no effect on the prime's efficiency, it is unlikely that sensory priming was involved. (4) The lack of a divergence between the effects of congruent and incongruent primes implies a functional difference between t
Keywords: perceptual latency priming; temporal order judgments; masked stimuli; unmasked stimuli; attentional interpretation; response times; location cueing; visual perception; Adult; Attention; Female; Humans; Male; Models; Psychological; Perceptual Masking; Psychometrics; Reaction Time; Task Performance and Analysis; Time Perception; Masking; Reaction Time; Response Latency; Stimulus Parameters; Visual Contrast; Attention; Cues; Priming; Temporal Frequency; Temporal Order (Judgment)

Temporal parameters and time course of perceptual latency priming. - Scharlau, Ingrid; Neumann, Odmar (Acta Psychologica)
Visual stimuli (primes) reduce the perceptual latency of a target appearing at the same location (perceptual latency priming, PLP). Three experiments assessed the time course of PLP by masked and, in Experiment 3, unmasked primes. Experiments 1 (N=11; mean age 26.9) and 2 (N=12; mean age 25.6) investigated the temporal parameters that determine the size of priming. Stimulus onset asynchrony was found to exert the main influence accompanied by a small effect of prime duration. Experiment 3 (N=19; mean age 27.7) used a large range of priming onset asynchronies. We suggest to explain PLP by the Asynchronous Updating Model which relates it to the asynchrony of 2 central coding processes, preattentive coding of basic visual features and attentional orienting as a prerequisite for perceptual judgments and conscious perception. (PsycINFO Database Record (c) 2017 APA, all rights reserved)
Keywords: perceptual latency priming; temporal parameters; Asynchronous Updating Model; time course; stimulus onset asynchrony; visual masking; attention; Adult; Attention; Female; Humans; Male; Perceptual Masking; Reaction Time; Time Perception; Visual Perception; Attention; Priming; Stimulus Onset; Visual Masking; Visual Perception; Models; Time

Discrete-Event Converter Control - Böcker, Joachim (EPE 2003, Graz)

Personale Bedingungen reziproker Eltern-Kind-Beziehungen - Buhl, Heike M. (Jugendzeit - Time out? Die Ausgestaltung des Jugendalters als Moratorium)